American afterlife : encounters in the customs of mourning - Sweeney, Kate, 1978- (The University of Georgia Press, 2014)
What happens after someone dies depends on our personal stories and on where those stories fall in a larger tale--that of death in America. It's a powerful tale that we usually keep hidden from our everyday lives until we have to face it. American Afterlife by Kate Sweeney reveals this world through a collective portrait of Americans past and present who find themselves personally involved with death: a klatch of obit writers in the desert, a funeral voyage on the Atlantic, a fourth-generation funeral director--even a midwestern museum that takes us back in time to meet our death-obsessed Victorian progenitors. Each story illuminates details in another until something larger is revealed: a landscape that feels at once strange and familiar, one that's by turns odd, tragic, poignant, and sometimes even funny.